Factors influencing acceptance of clinical decision support systems among healthcare professionals in Malaysia - Esmaeilzadeh, Pouyan (2011)
A variety of Health Information Technology Systems (HITS) in the form of clinical information technology have gradually become established in the healthcare industry. Clinical information technology is considered as a strategic healthcare tool to improve the quality of health care service, the efficiency and effectiveness of healthcare professionals in the health care sector. Clinical Decision Support (CDS) systems are mainly used to assist healthcare professionals (such as physicians and specialists) in decision making and improving the quality of healthcare delivery. If CDS systems are not fully used by healthcare professionals, the effort and investment are doomed to failure. There are concerns regarding the adoption of CDS among healthcare professionals in Malaysia. However, factors affecting healthcare professionals’ adoption behavior related to using CDS are still not completely clear. The technology adoption models such as UTAUT are not specially targeted at healthcare professionals and they do not include the unique characteristics of healthcare professionals as well as special features and properties of CDS. The central characteristic of healthcare professionals that is considered in this research is professional autonomy. The special features and properties of CDS that are considered in this research are: 1- the level of knowledge codification and knowledge distribution and 2- guidelines and instructions generated by CDS and the level of interactivity between healthcare professionals and the CDS system.Integration of the healthcare professionals’ characteristics with features of CDS can provide a better understanding on IT adoption in the special context of healthcare practice. For this p rpose, the original version of the UTAUT has been extended with physician’s unique characteristics and special characteristics of CDS systems. This study thus proposes a research framework from a broader and an integrated perspective. To confirm the proposed framework 21 semi-structured interviews with some specialists (from different fields) were conducted in Malaysian hospitals. Furthermore, a survey has been used to evaluate the hypothesized model among 309 healthcare professionals in Malaysia. The structural equation model has been used to test the model in this context. The results stress the importance of perceived threat to professional autonomy, physicians involvement in decision making in CDS planning as well as implementation and also cognitive instrumental processes (mainly, usefulness perceptions) in determining physicians’ intention to use CDS systems. The empirical examination shows high predictive power for adoption intention and the influential role of these important variables. A recent study on usage of EMR based on the original UTAUT shows that the model can explain only 20% of the variance in the usage intention of EMR whereas the proposed model of this study can explain 47% of the variance of healthcare professionals’ behavioral intention in the CDS setting. The explanatory power of the proposed model indicates that the unique characteristics of physicians have a strong and statistically significant influence on physicians’ usage intention. This study adds to the body of knowledge on IT adoption models and sheds some new insights into technology acceptance models amongst healthcare professionals by finding unique factors affecting healthcare professional’s intention to accept the CDS system. Moreover, with this understanding, managers and practitioners are in a better position not only to identify the source of resistance toward the new CDS but also to devise strategies to improve the overall acceptance of the system among healthcare professionals in a hospital setting.